Sources and Prevalence of Aflatoxin B1 in Different Rice Paddies of Punjab and Sindh, Pakistan - Adrees, Usman; Afzal, Imran; Chaudhary, Ahmed Shabbir; Zia, Ramna; Ali, Kashif; chaudary, Hassan shabbir (BioScientific Review, 2023)
Rice is a major cash crop used all over world. The hygroscopic nature of rice kernel with warm and fumic conditions is favorable to enhance the growth and development of toxigenic fungi which produce mycotoxins. This study estimates the prevalence of aflatoxin B1 in different rice paddies collected from twelve regions of the Punjab and Sindh provinces of Pakistan. All the samples were analyzed for their phenotypic characteristics (appearance, odor, and grain length). Competitive Enzyme Linked Immuno Sorbent Assay (ELISA) was used to evaluate AFB1, both before and after applying the steam decontamination procedure to detoxify aflatoxin contamination. Cultural assay was used to find the source of aflatoxin. PDA and SDA agar were used to detect aflatoxin producing fungal species. Lactophenol Cotton Blue (LCB) staining was used for microscopic identification of fungal contaminants. Paddies from most regions appeared yellowish in color and odorless with the exception of Hafizabad, Jhang, Sheikhupura, and Gujarat (in Punjab), where they appeared blackish yellow in color and with a pungent smell. According to the results, 43 (61.42%) samples were detected with aflatoxin B1 out of 70 samples, with an average of 15.86±1.7 ug/kg, before treating with seam. After treatment with steam, 7 (10%) samples were detected with aflatoxin B1, with an average of 2.55±1.51 ug/kg. Most regions showed the presence of P. chrysogenum with the exception of R.Y. Khan, which showed the presence of A. niger. Steam, on average, reduced aflatoxin to 51.42%. The current study indicates that steam is an effective treatment to eradicate aflatoxin at industrial level. New approaches may be explored to target the contaminants in order to ensure food safety.